Quantum computing in action - Vos, Johan (Manning, 2022)
Quantum computing promises unimaginably fast performance for tasks like encryption, scientific modeling, manufacturing logistics, financial modeling, and AI. Developers can explore quantum computing now using free simulators, and increasingly powerful true quantum systems are gradually becoming available for production use. This book gives you a head start on quantum computing by introducing core concepts, key algorithms, and the most beneficial use cases. "Quantum computing in action" is a gentle introduction to the ideas and applications of quantum computing. After briefly reviewing the science that makes quantum tick, it guides you through practical implementations of quantum computing algorithms. You'll write your first quantum code and explore qubits and quantum gates with the Java-based Strange quantum simulator. You'll enjoy the interesting examples and insightful explanations as you create quantum algorithms using standard Java and your favorite IDE and build tools
Auf dem Einband: "Examples in Java"
Keywords: Quantum computing; Java (Computer program language); Informatique quantique; Java (Langage de programmation)